2017
DOI: 10.1097/pec.0000000000001106
|View full text |Cite
|
Sign up to set email alerts
|

Missed Fractures in Infants Presenting to the Emergency Department With Fussiness

Abstract: Fractures concerning for child abuse are an important cause of unexplained fussiness in infants presenting to the pediatric ED. A high index of suspicion is essential for prompt diagnosis and likely prevention of other abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
12
0
2
Order By: Relevance
“…Nineteen (26%) studies focused specifically on injury patterns of abused children, and the likelihood of child abuse among patients presenting with fractures, head trauma, and oral injuries. 71 , 75 , 81 , 82 , 86 , 91 , 95 , 97 , 99 , 101 , 107 , 109 111 , 113 , 115 , 117 , 119 , 127 About 22 (31%) studies focused specifically on child sexual assault cases, 70 , 79 , 80 , 96 , 98 , 106 , 112 , 116 , 118 , 120 , 123 , 125 , 130 , 132 , 133 , 141 with six of these studies looking at sexually transmitted infection (STI) and pregnancy testing, STI prophylaxis, and the use of sexual assault nurse examiners. 77 , 78 , 121 , 122 , 140 , 150 Two of three review publications focused on screening, 154 , 155 with one publication focusing on improving the ED workflow for suspected or confirmed child abuse cases.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen (26%) studies focused specifically on injury patterns of abused children, and the likelihood of child abuse among patients presenting with fractures, head trauma, and oral injuries. 71 , 75 , 81 , 82 , 86 , 91 , 95 , 97 , 99 , 101 , 107 , 109 111 , 113 , 115 , 117 , 119 , 127 About 22 (31%) studies focused specifically on child sexual assault cases, 70 , 79 , 80 , 96 , 98 , 106 , 112 , 116 , 118 , 120 , 123 , 125 , 130 , 132 , 133 , 141 with six of these studies looking at sexually transmitted infection (STI) and pregnancy testing, STI prophylaxis, and the use of sexual assault nurse examiners. 77 , 78 , 121 , 122 , 140 , 150 Two of three review publications focused on screening, 154 , 155 with one publication focusing on improving the ED workflow for suspected or confirmed child abuse cases.…”
Section: Resultsmentioning
confidence: 99%
“…Without these surveillance mechanisms and regular pediatric checkups, more children are presenting to emergency departments (ED) with signs of maltreatment (Sidpra et al, 2020). This requires ED providers to recognize abuse within their differential diagnosis in order for child abuse reports and referrals to be made, even when patients are presenting with nonspecific chief complaints (Jenny et al, 1999;Kondis et al, 2017;Sheets et al, 2013). EDs and other acute care settings have been identified as sources of missed child maltreatment-related presentations due to failure to consider abuse within the differential diagnosis, lack of training, fear of losing clientele, and aversion to involvement in legal processes (Gunn et al, 2005;Jenny et al, 1999;Keshavarz et al, 2002;Pierce et al, 2017;Sheets et al, 2013).…”
Section: Covid-19's Impact On Child Maltreatment and Medical Settingsmentioning
confidence: 99%
“…There were 27 studies that reported on the specific keywords that were present within the narratives [ 38 - 41 , 43 , 79 , 81 , 83 , 86 , 89 - 93 , 95 , 99 , 101 , 102 , 104 , 107 - 111 , 117 , 118 , 125 , 126 , 131 ]. The number of keywords ranged from 1 [ 101 ] to >160 [ 39 ], with a median number of 11 (IQR 3-24.5) keywords reported ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, 11% (3/27) of studies did not report the exact number of keywords used [ 38 - 40 ]. The authors reported the use of express keywords with correct spellings [ 86 , 93 , 101 , 107 , 109 - 111 ] as well as intentional variations such as misspellings, abbreviations, or truncations [ 39 , 40 , 81 , 92 , 108 ]. One of the studies searched for terms using keywords in 2 languages (English and French) [ 95 ].…”
Section: Resultsmentioning
confidence: 99%